Revoking Russia’s MFN status as an Instrument of Western Sanctions Pressure: Impact on Trade and Logistics - E. Ya. Arapova; E. S. Knyazkina (Международная аналитика)
In March 2022 several G7 countries and their trading partners announced the suspension of the most-favored-nation (MFN) status for imports from Russia. The MFN used to be a fundamental rule of multilateral trade regulation within the World Trade Organization (WTO). The article provides a qualitative analysis of the role of MFN status in the modern international trade system, as well as the impact of the suspension of MFN status on Russian foreign trade and logistics.Among the countries that suspended MFN status for imports from Russia, the European Union (EU) represented the most significant export destination. It was found that, in addition to the energy sector, industries that have experienced the most significant reductions in exports to the EU include ferrous and non-ferrous metalls, precious metals production, and timber and wood products manufacturing. At the same time, an important trend is observed: anticipating further sanctions escalation, certain sanctioning countries (primarily EU member states) demonstrated an increase in the import of specific goods in 2022. This primarily concerned metals such as copper, aluminum, nickel, and products made from them, as well as fertilizers. The statistics of 2023 show a more significant and comprehensive reduction in Russian exports to the EU, yet this was accompanied by a significant compensatory effect of Russia’s redirecting exports from Western markets towards trade partners in the East (both in 2022 and 2023). The logistics crisis of the first months following the onset of sanctions attacks was largely overcome by the end of 2022. In relative terms, the most severe impact was on air cargo transportation, while sanctions played a key role in the re-equipping and optimization of major railway and sea logistics centres.